The Relationship Between Social Support, Self-Efficacy and Procrastination and Student Academic Stress in Distance Learning During the Covid-19 Pandemic - Lisnawati Ruhaena; Wahyu Mahardika Indrayanti (Journal of Social Interactions and Humanities, 2024)
In the midst of the pandemic, changes in the education system at all levels have become a necessity. Face-to-face classroom learning has shifted to distance learning, utilizing various media tools such as Schoology, Zoom, and others. This change has brought significant impacts on students, one of which is the increased level of academic stress. Academic stress can be influenced by various factors, including self-efficacy and the tendency to procrastinate, as well as social support from the surrounding environment. The aim of this research is to examine the relationship between social support, self-efficacy, academic procrastination, and academic stress experienced by students during distance learning. This study employs a quantitative correlational method, involving 408 undergraduate students at Universitas Muhammadiyah Surakarta. Respondents were randomly selected using criteria that they had participated in distance learning during the COVID-19 pandemic. The collected data were then analyzed using multiple linear regression analysis. The results of the study indicate that social support, self-efficacy, and academic procrastination are correlated with academic stress, with a correlation coefficient (R) of 0.442 and an effective contribution of 19.6%.